EFFICIENT MARKET HYPOTHESIS TEST WITH SPECIAL REFERNCE TO THE INDIAN TELECOM INDUSTRY - Anand, Sumit (International Journal of Psychosocial Rehabilitation, 2020)
This empirical study is based on the statistical comparison of the Indian Telecom players with refers its share price movements on the Indian Stock Market i.e. BSE (Bombay Stock Exchange). Various statistical tools have been applied to measure their performance such as mean, median. Standard deviation, standard error, variance, RMS, quartiles, skewness, kurtosis, regression and one way Annova. The data under study has been taken for one month i.e. January 2020 (30 days in which only 23 days were working). So we have 23 data set for all players. The examples include airtel, Vodafone, reliance jio and MTNL.